I'll do problem 5 to get you started.
The answer is choice B and choice D
The reason why choice B is one answer is because we have something in the form y = k/x to indicate an inverse variation. Replace x with H and y with T, and you'll get the same basic equation.
With inverse variation equations, as one variable goes down, the other variable goes up. Think of a see-saw as one way to visualize what's going on.
Or you can think of the T as T/1. So the equation T = L/H is the same as T/1 = L/H. If H were to decrease, then T would increase, and vice versa. T and H are on opposite sides of their respective fractions which may help see this opposite moving nature of each variable.
The reason why choice D is also an answer is because we can multiply both sides of T = L/H by H to get HT = L or TH = L. The equations T = L/H and TH = L are equivalent equations.